Synthesis and Characterization of Propofol-Like Compounds, Anticancer Activities and Investigation of Their Anesthetic Effects by Molecular Docking - Demirci, Serpil; Uslu, Harun; Mermer, Arif; Yesilay, Gamze; Betul Aydin, Zehra (John Wiley and Sons Inc, 2024)
This study was designed to synthesize hybrid molecules starting from 2,6-diisopropyl aniline (1), which is similar to Propofol (2,6-diisopropyl phenol), by increasing its biological activity with other heterocycles and to determine the anesthetic activity of the obtained compounds. For this purpose, commercially available 2,6-diisopropylaniline (1) was used as a starting compound. Then, ester (2), hydrazide (3), carbothioamide (5, 6) and Schiff bases derivatives (4 a–f) were synthesized, respectively. To achieve the etomidate-like target compound 8, compound 7 containing chloroacetamide group was firstly synthesized from starting compound 1, and this compound reacted with ethyl-1H-imidazole-5-carboxylate. The structures of the newyl synthesized 12 compounds were characterized and confirmed by FT-IR, MALDI-TOF/MS, 1H NMR, 13C NMR. Within the scope of in silico study, ligand binding status of all compounds on the GABAA receptor was revealed. Molecular docking studies of them with GABAA found out that the interaction modes, including van der Waals interactions, hydrogen bonds, and pi-pi interactions, are similar to that of the cocrystalline ligand Propofol. For the compounds 1, 2, 3, 4 d, 5, 7 have micromolar (?M) level, for the compounds 4 a, 4 b, 4 c, 4 e, 4 f, 6 and 8 have nanomolar (nM) level of inhibition has been estimated. When all data such as active localization, interacting residues, bond types formed, estimated Ki values, docking scores are evaluated together, compounds 1, 2, 3 and 7 which can be considered as synthesis starting or intermediate material, may be less effective. On the other hand the anticancer activities of the synthesized compounds were investigated against A549 (non-small cell lung carcinoma) and BEAS-2B cell line (normal bronchial epithelial) cell lines using Resazurin cell viability assay. It has been revealed that the compounds 4, 5, 6 and 8 may be more active in terms of anesthetic activity, whereas only compound 6 showed anti-cancer activity. © 2024 Wiley-VCH GmbH.
Keywords: Anesthetic effect; Anticancer activity; Carbothioamide; Molecular docking; Propofol; Schiff base